High rates of SARS-CoV-2 infection in funeral home workers in Ecuador: Is it an occupational risk for COVID-19? - Ortiz-Prado, Esteban; Vásconez, Jorge Eduardo; Vallejo-Janeta, Alexander Paolo; Morales-Jadán, Diana; Henriquez-Trujillo, Aquiles R.; Rivera-Olivero, Ismar A.; Andrade, Felipe; Lozada, Tannya; Garcia-Bereguiain, Miguel Angel; , UDLA COVID-19 Team (Frontiers in Public Health, 2022)
Aim The COVID-19 outbreak has already caused more than 6.5 million deaths, overwhelming health systems worldwide. The unusual demand for funeral home services could make these workers a potential risk group for occupational exposure to SARS-CoV-2 associated with corpses management for COVID-19 patients. Methodology This is a cross-sectional study aimed to describe the infection rate of SARS-CoV-2 in funeral home staff by testing them with RT-qPCR in Quito, Ecuador. A total of 232 funeral home workers, representing more than 40% of funeral home personnel in Quito, were included in the study, in June 2020, immediately after the population lockdown was lifted in Ecuador. Results A total of 48 individuals tested positive for SARS-CoV-2, yielding an infection rate of 20.7%. The SARS-CoV-2 infection rate was 18.1 and 20.0% among personnel managing corpses or not managing corpses, respectively. Among the SARS-CoV-2 positive patients, 81.3% reported no symptoms related to COVID-19, and 3 individuals had high viral loads over 108 copies/ml. Conclusion The high SARS-CoV-2 infection rate in funeral home staff suggested a potential occupational risk for COVID-19 but not related to corpses management. Public health guidelines for safe corpses management for COVID-19 victims and safe funeral services should be reinforced.